Teaching methodologies in Genetics: A literature review on the content of ABO and Rh Systems (Research, Society and Development, 2024)
The use of various teaching approaches can improve the understanding of the ABO and Rh systems content in the teaching of Genetics, given the complexity and abstract nature of these topics addressed in the classroom. It is up to teachers to seek more playful ways to explore these subjects, such as actions, methods, or environments that encourage learning and development through fun, interactive, and stimulating activities, using different methodologies to facilitate students' comprehension. This study is a literature review focused on the use of teaching methodologies in Genetics, specifically on the ABO and Rh systems. The objective was to identify the methodologies employed in high schools and to contribute to discussions on how to promote more effective teaching of these topics, enhancing students' learning techniques. For this purpose, a search was conducted on the Google Scholar platform, and after analysis, 28 articles were selected for this review. The exploration of academic sources allowed for the analysis of the effectiveness and impact of methodologies such as practical activities, technological resources (digital games, software, applications), and didactic sequences on the understanding of genetic concepts. The research highlighted the importance of these methodologies in making teaching more accessible, stimulating student engagement, and catering to different learning styles. By synthesizing the contributions of specialized literature, this study offers valuable insights for educators and researchers interested in improving the quality of Genetics teaching through innovative and effective approaches.